Building Teacher Self-Efficacy: A University/District Leadership Academy Model - Donna Augustine-Shaw; Mary Devin (The Advocate, 2014)
Introduction: In an era dominated by higher standards and greater accountability for America’s If you want to join us, we would be delighted schools, leaders are needed at all levels. Teachers must continue learning and growing professionally long after that transition from pre-service to practitioner.